Evaluation of Autogenous Avibacterium paragallinarum Bacterins in Chickens - El-Ghany, Wafaa A. Abd (International Journal of Poultry Science, 2010)
In this investigation, a trial for preparation and evaluation of locally prepared (autogenous) bacterin against the infection with Avibacterium paragallinarum (Avi. paragallinarum) causing infectious coryza disease in layer chickens was done. Two types of adjuvant (aluminum hydroxide and mineral oil based) were compared. At 6 weeks of age, one hundred layer chickens were divided into equally distributed 4 groups each containing 25 birds. Group (1) was vaccinated with Avi. paragallinarum autogenous bacterin containing aluminum hydroxide, while group (2) received Avi. paragallinarum autogenous bacterin containing mineral oil. Both types of bacterins were given in a dose of 0.5 ml/bird and administered intramuscularly (IM). Booster dose of both types of the autogenous bacterins was given in group 1 and 2 at 9 weeks of age. Chickens of group (3) were kept without vaccination. Birds in groups 1, 2 and 3 were challenged with (106 CFU) of live Avi. paragallinarum culture by inoculation into the nasal sinus at 12 weeks old. Group (4) was left as blank control negative (not vaccinated or challenged). Birds after challenge were kept under complete daily observation for 7 days. Signs, mortalities, postmortem lesions, protection rate and reisolation rate of the organism were taken as criteria for bacterin evaluation, also agglutination test were performed on sera to determine the immune response to bacterin at the doses intervals. The results revealed that whatever the type of adjuvant, both different adjuvanted types' bacterines were effective and safe in prevention of infection against Avi. paragallinarum in layers when administered at 6 and boosted at 9 weeks of age.